Turmeric: A Spice Modulating Immune Response and Combatting Cancer - literature overview - Anna; Bartosz Mazur; Karol Stachyrak; Dawid Mika; Aleksandra Kłos; Kamila Turek; Maciej Lambach; Mateusz Pawlicki; Aleksandra Mazurek; Wiktoria Wilanowska (Kazimierz Wielki University, 2024)
Introduction Curcumin, the active ingredient in turmeric, is gaining increasing attention due to its potential health benefits, especially in the context of its immunomodulatory and anticancer properties. Aim of the study The aim of this review was to discuss recent findings regarding the impact of curcumin on the immune system and its potential applications in anticancer therapy. Materials and methods The paper was created based on the Pubmed and Scholar database. The literature was reviewed using the keywords: "curcumin", "immunomodulatory effects", "cytokines", "anticancer", "apoptosis", "cell proliferation", "radiosensitizing". Results Studies have confirmed that curcumin, especially in the form of nanocurcumin, exhibits significant immunomodulatory effects. It reduces the number of Th17 cells, increases Treg cells, and regulates the expression of pro-inflammatory cytokines, which is crucial in controlling autoimmune reactions. Furthermore, it demonstrates anticancer activity by inhibiting the growth of cancer cells, stimulating apoptosis, and enhancing the effectiveness of anticancer therapy. Conclusions Despite promising results, further research on the safety of curcumin therapy, particularly in the long term, is essential. Limitations associated with bioavailability and pharmacokinetics suggest the need for the development of formulations with increased bioavailability to maximize the potential benefits of curcumin in the treatment of various disorders.